Breast Cancer Patients With Positive Apical or Infraclavicular/Ipsilateral Supraclavicular Lymph Nodes Should Be Excluded in the Application of the Lymph Node Ratio System - Wang, Zhe; Chong, Wei; Zhang, Huikun; Liu, Xiaoli; Zhao, Yawen; Guo, Zhifang; Fu, Li; Ma, Yongjie; Gu, Feng (Frontiers in Cell and Developmental Biology, 2022)
Purpose: Increasing studies suggested that lymph node ratio (LNR) could be an accurate prognostic indicator in breast cancer and LNR could be considered as an alternative to pN staging; however, the AJCC-TNM staging system classified apical or infraclavicular/ipsilateral supraclavicular lymph nodes positive (APN (+)) patients who had worse prognosis into pN3 stage. Until present, the different reports about LNR in breast cancer ignored this possibility. Consequently, it was necessary to discuss about the role of APN (+) patients in the LNR system to obtain precise LNR which predicted the prognosis accurately. Materials and Methods: We collected 10120 breast cancer patients including 3936 lymph node positive patients (3283 patients and 653 APN (+) patients) ranged from 2007 to 2012 in our hospital. Then we applied X-tile analysis to calculate cut-off values and conduct survival analysis and multivariate analysis to evaluate patients’ prognosis. Results: We confirmed that some APN (+) patients could been mis-subgrouped according to previously reported LNR, indicating that APN (+) patients should be excluded in the application of LNR to predict prognosis. Then we applied X-tile analysis to calculated two cut-off values (0.15 and 0.34) for LNR-APN (-) and conducted survival analysis to find that LNR-APN (-) was superior to pN stage in predicting prognosis of breast cancer patients with APN (-). Conclusion: Our present study revealed that excluding APN (+) patients is the most necessary supplement to LNR system. LNR-APN (-) could be a more comprehensive approach to predict prognosis and guide clinicians to provide accurate and appropriate treatment.